The Global Landscape of Addictions: How Does Tourism Influence Modern Addictive Behaviors? - Csapi, Patrik (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
In my research, I aimed to provide a comprehensive overview of the global prevalence of various types of addictions and to examine how these may relate to the intensity and economic significance of tourism. My analysis included not only classical chemical addictions—such as alcohol, cannabis, and cocaine—but also modern behavioral addictions, including internet and gaming addiction, gambling, compulsive shopping, workaholism, eating disorders, and sex addiction. By analyzing country-specific prevalence data and supplementing this with cultural and psychological explanations, I explored which societies exhibit particularly high rates of addiction and why. I paid special attention to the extent to which tourism may influence the occurrence of specific addictions—and found that while certain addictions (e.g., cannabis use, sex addiction, gambling) may indeed be linked to inbound tourism, others (such as workaholism or eating disorders) are more closely tied to internal socio-economic and cultural factors. My findings highlight that the geographical distribution of addictions is shaped more by cultural norms, social structures, and local economic conditions than by tourism activity. In conclusion, I propose directions for further interdisciplinary research and emphasize the importance of comprehensive prevention and treatment strategies in an increasingly globalized and digitalized world.